Development and Validation of a Measure of Birth-Related PTSD for Fathers and Birth Partners: The City Birth Trauma Scale (Partner Version) - Webb, Rebecca; Smith, Ann M.; Ayers, Susan; Wright, Daniel B.; Thornton, Alexandra (Frontiers in Psychology, 2021)
Research suggests that some fathers and birth partners can experience post-traumatic stress disorder (PTSD) after witnessing a traumatic birth. Birth-related PTSD may impact on many aspects of fathers’ and birth partners’ life, including relationship breakdown, self-blame and reducing plans for future children. Despite the potential impact on birth partners’ lives there is currently no measure of birth-related PTSD validated for use with birth partners. The current study therefore adapted the City Birth Trauma Scale for use with birth partners. The City Birth Trauma Scale (Partner version) is a 29-item questionnaire developed to measure birth-related PTSD according to DSM-5 criteria: stressor criteria (A), symptoms of re-experiencing (B), avoidance (C), negative cognitions and mood (D), and hyperarousal (E), as well as duration of symptoms (F), significant distress or impairment (E), and exclusion criteria or other causes (H). A sample of 301 fathers/birth partners was recruited online and completed measures of birth-related PTSD, bonding, and demographic details. Results showed the City Birth Trauma Scale (Partner version) had good reliability (α = 0.94) and psychometric and construct validity. The fathers/birth partners version has the same two-factor structure as the original scale: (1) general symptoms and (2) birth-related symptoms, which accounted for 51% of the variance. PTSD symptoms were associated with preterm birth and maternal and infant complications. Overall, the City Birth Trauma Scale (Partner version) provides a promising measure of PTSD following childbirth that can be used in research and clinical practice.